Methyl Thiazolyl Tetrazolium Cell Viability Assay and Intracellular Reactive Oxygen Species Activity of an Ethanol Extract of Eclipta prostrata L.: Methyl Thiazolyl Tetrazolium Cell Viability Assay and Intracellular Reactive Oxygen Species Activity of an Ethanol Extract of Eclipta prostrata L. - Devi, D. Nalini (International Journal of Pharmaceutical & Biological Archive, 2018)
Anti neoplastic effect of Eclipta prostrata L. (HepG2) cell lines. Hepatocellular carcinoma (HCC) is a tumor of the liver. HCC is responsible for over 12,000 deaths per year in the United States. It is one of the serious health problems in most developing countries. The present probe proved that ethanol extract of Eclipta prostrata L. significantly suppressed the growth and induced the apoptosis in the liver cancer (HepG2) cell lines. IC50 dose was measured with methyl thiazolyl tetrazolium. 100 Î¼g of extract showed 50% reduction of in HepG2 cell line growth at 48 h of incubation. The whole plant of E. prostrata L. extract-induced apoptotic features of cell death was stained with acridine orange. The intracellular enzymatic antioxidants such as superoxide dismutase, glutathione peroxidase, and catalase were slightly decreased in their activities when compared to control. Thus, the study resolves that E. prostrata L. extract is an effective to prevent or retard the spread of malignant cells and antineoplastic effect.